IMPLEMENTASI TEXT SUMMARIZATION REVIEW APLIKASI TOKOPEDIA DI GOOGLE PLAYSTORE MENGGUNAKAN ALGORITMA TEXT RANK - Maharani, Bryliana Delvia; Budianto, Alexius Endi; Harianto, Wahyudi (Jurnal Fakultas Teknologi Informasi, 2025)
How does text summarization work in reviewing the Tokopedia application Google Play Store How to implement the text rank algorithm in doing so text summarization in the Tokopedia application review on Playstore. Measuring accuracy and the performance of the text rank algorithm in text summarization in the Tokopedia application review in google playstore How effective is the textrank algorithm when used for text summarization A framework is a structure used to help researchers or thinkers in compiling and understanding information systematically.collect data by scraping data on Google Collab, scraping data, Observation is a data collection method by observing events. The data collection method used in creating this system was literature study. Literature studies are carried out by processing information related to manufacturing system, making notes sourced from library materials. Evaluation results using ROUGE shows that this method is effective in extracting important information from the review, allowing to produce a summary that relevant and informative with a recall accuracy value of 93.78%. results in summarizing text in reviews Tokopedia application on the Play Store. By building a weighted graph from matrices cosine similarity based on TF-IDF vector representation.